KONSEP DASAR JURNALISME PEMBANGUNAN - Sumaina Duku (Wardah, 2014)
Journalism is an activity related to gather, write, edit and present the news through print media or electronic media while development is understood as a process of change for the better through the efforts made in general terencana. Goal of development is the furthest projection of expectations  and human ideas, the components of which is the best possible, or ideal society that can best special. Objectives  is the development of short-term goals, usually chosen as the level of achievement of the objectives of a certain program. Jurnalisme development is emerging journalistic style or Third World countries that promotes the role of the press in the context of national development. Development journalism is often exploited or used by the leaders of developing countries to achieve the goals and interests of its political development. Jurnalisme or "journalism of development" is journalism that aims to provide an understanding of the development of society. Development journalism convince society of the future, so that they can participate in the development.